PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR), UKURAN PERUSAHAAN DAN KONEKSI POLITIK TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Periode 2017-2019) - , Supriono, Febri Mayarni , Zirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine and analyze the effect of Corporate Social Responsibility (CSR), Company Size and Political Connections on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2017-2019 Period. For the Corporate Social Responsibility check list, it refers to the Global Reporting Initiative (GRI). Firm size variable is measured by the natural logarithm (Ln) of total assets. Political connection variable can use dummy number 1 and number 0 . While the dependent variable tax avoidance is measured by measuring the effective tax rate (Effective Tax Rate). This research includes quantitative research. The total population in this study was 178 auditors at Manufacturing Companies Listed on the IDX for the 2017-2019 period. The sampling technique used is purposive sampling. So that 31 companies were selected according to predetermined criteria for 3 years and a sample of 93. The data were analyzed using multiple regression analysis using SPSS 26. The results of this study indicate that Corporate Social Responsibility (CSR), Company Size and significant effect on Tax Avoidance. The political connection variable has no effect on Tax Avoidance. Keywords : Corporate Social Responsibility (CSR), Company Size, Political Connections and Tax Avoidance.